1974
DOI: 10.1159/000180389
|View full text |Cite
|
Sign up to set email alerts
|

A Mini-Epidemic of Goodpasture’s Syndrome

Abstract: Four patients who developed symptoms of Goodpasture’s syndrome during the winter 1971–1972 from a geographic area of about a 25mile radius have been studied. There was an epidemiological association between these cases and a concurrent outbreak of influenza A2; however, corroborative virologic or serologic evidence could not be obtained. All patients had typical clinical manifestations of severe pulmonary and renal disease. Immunofluorescence studies revealed linear deposits of IgG in all glomeruli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Anti-GBM disease is reported to have the highest rate of crescentic glomeruli at the time of diagnosis [ 4 ]. While environmental factors have been suspected to play a role in the pathogenesis others have reported infection as an inciting factor; however, no clear infective pathogenic association has been identified [ 5 , 6 ]. Multiple case reports also suggest a possible link between hydrocarbon exposures [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-GBM disease is reported to have the highest rate of crescentic glomeruli at the time of diagnosis [ 4 ]. While environmental factors have been suspected to play a role in the pathogenesis others have reported infection as an inciting factor; however, no clear infective pathogenic association has been identified [ 5 , 6 ]. Multiple case reports also suggest a possible link between hydrocarbon exposures [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…We tested the effects of IL-2 and IFN-a because Puri and Rosenberg have shown that the association of IL-2 and IFN-a induces in mice the most severe vascular leak syndrome in the lung, whereas IFN-'y and tumor necrosis factor-a do not exert a similar effect when given alone, nor act synergistically with IL-2 (1 1). Moreover, the use of IFN-a was motivated by the consideration that epidemic (26,27) or sporadic (28) outbreaks of influenza or other acute infections (2) have been traditionally associated with Goodpasture's hemorrhagic pneumonitis, and IFN-a is induced by viral infection (29).…”
Section: Discussionmentioning
confidence: 99%
“…Eleven patients were found to participate in this study. For each of these patients, we retrospectively determined clinical features including age at diagnosis of hydronephrosis, sex, medical history of preexisting renal disease, especially membranous nephropathy, causes of hydronephrosis and the presence or absence of clinical risk factors for the development of anti-GBM antibodies such as smoking history, exposure to organic solvents, recent infection prior to the onset of renal impairment and enforcement of ESWL [ 4 , 5 , 6 , 7 , 10 ]. We also investigated their serum creatinine (sCr mg/dl), the degree of hematuria shown as the number of urinary red blood cells (RBCs) per high-power field (HPF), the deformity of urinary RBCs and RBC cast formation and titer of serum anti-GBM antibodies before and after treatment for hydronephrosis.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the available evidence, it is hypothesized that a disruption of the stabilized NC1 hexamer and exposure of the cryptic antigen of the α3-chain to the host immune system are required for the development of anti-GBM antibodies [ 3 ]. Several studies have proposed causes for the modifications of intact NC1, namely smoking, infections, exposure to organic solvent and enforcement of extracorporeal shock wave lithotripsy (ESWL) [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%